Comparison of Pulegone and Estragole Chemotypes Provides New Insight Into Volatile Oil Biosynthesis of Agastache rugosa - Dang, Jingjie; Lin, Guyin; Liu, Licheng; Zhou, Peina; Shao, Yongfang; Dai, Shilin; Sang, Mengru; Jiang, Zheng; Liu, Chanchan; Wu, Qinan (Frontiers in Plant Science, 2022)
The aerial parts of Agastache rugosa are rich in essential oils containing monoterpenoids, phenylpropanoids, and aromatic compounds. These are used as herbs, perfume plants, and ornamental plants. Based on the difference in the constituents of the essential oil, A. rugosa is divided into pulegone and estragole chemotypes, but the mechanism of key metabolite biosynthesis in these two A. rugosa chemotypes remains unclear. In this study, we compared the morphological differences, metabolite constituents, and transcriptomic data between the two chemotypes of A. rugosa. Monoterpenoid was the main compound in the pulegone chemotype, and phenylpropanoid was the main compound in the estragole chemotype; however, limonene was detected in both chemotypes. Furthermore, 46 genes related to pulegone and estragole biosynthesis were identified. Limonene synthase, limonene-3-hydroxyase, and isopiperitenol dehydrogenase were upregulated in the pulegone chemotype, while phenylalanine ammonia-lyase, 4-coumarate: CoA ligase, CYP73A, coumaroyl-aldehyde dehydrogenase, and eugenol synthase were downregulated in the pulegone chemotype. We identified chavicol methyl transferase and limonene-3-hydroxylase in A. rugosa. This work not only provides the difference in morphology and metabolites in pulegone and estragole chemotypes, but also offers a molecular mechanism of volatile oil biosynthesis, which could be a basis for specialized metabolites in specialized chemotypes.